2013
DOI: 10.1080/07399332.2013.770003
|View full text |Cite
|
Sign up to set email alerts
|

“I Get Angry If He's Always Drinking and We Have No Money”: Exploring Motivations for Male and Female Perpetrated Intimate Partner Violence in the Philippines

Abstract: Our objective was to describe the context of and motivations for female and male perpetrated IPV in Cebu, Philippines using data from in-depth interviews with 19 married women. We found three categories of IPV motivations --self-defense or retaliation, reactivity, and control. Motivations differed by gender, with women acting out of self-defense more often and men acting out of control more often. Effective IPV prevention and treatment programs should take these gender differences into consideration. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
2
18
0
2
Order By: Relevance
“…We found that IPV is a common problem in the study setting. When exploring common triggers of IPV, we found that jealousy, financial strain and men’s alcohol consumption were most often cited; this is consistent with other studies from the region [ 28 , 31 – 33 ]. Reducing conflicts over money and financial stress appeared to be one of the main ways in which the transfers helped reduce IPV.…”
Section: Discussionsupporting
confidence: 90%
“…We found that IPV is a common problem in the study setting. When exploring common triggers of IPV, we found that jealousy, financial strain and men’s alcohol consumption were most often cited; this is consistent with other studies from the region [ 28 , 31 – 33 ]. Reducing conflicts over money and financial stress appeared to be one of the main ways in which the transfers helped reduce IPV.…”
Section: Discussionsupporting
confidence: 90%
“…However, IPV is the most current term used to refer to violence between intimate partners who may or may not be married. The use of this term also recognises that IPV can happen in heterosexual as well as homosexual relationship and that women can also be perpetrators of IPV (Desmarais et al 2012, Fehringer & Hindin 2014. While it is established that women can perpetrate IPV against their male partners, the number of women experiencing IPV and/or sustaining injuries is much higher (Howarth et al 2013, World Health Organisation 2015.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…The case of intimate partner violence in Cebu, for instance, is associated with alcohol use among men partners. Women partners, in this case, are also motivated to inflict physical injury to their husband or partner out of self-defense while their partners act out of control more often (Fehringer & Hindin, 2014). Hence, crime can also be caused by psychological elements outside of an individual"s control (Vito & Maahs, 2015).…”
Section: Resultsmentioning
confidence: 99%